(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The dynamic process of language evolution has contributed to the introduction of many word combinations from different cultures into the English language, enriching and improving its lexicon with various expressions and concepts. Among these influences, the linguistic integration of foreign words of Turkic origin, which occurs as a result of historical, geographical and socio-political interactions between the Turkic-speaking world and English-speaking communities, is closely related to psychological factors in the process of word acquisition. This article explores the division of Turkic words of Turkic origin into separate semantic domains such as objects, food, titles, names, animals, drinks, technological devices, gadgets, plants, etc. Furthermore, the article analyzes whether these words entered English directly from Turkish or through intermediary languages, and examines the sociocultural and psycholinguistic reasons behind their adoption. It should be noted that this issue has not only psycholinguistic but also psycholinguistic aspects, which require separate research, highlighting the multifaceted nature of cross-linguistic influence, and providing insight into the broader implications of linguistic borrowing in the context of globalization.